A better understanding of seawater reverse osmosis brine: Characterizations, uses, and energy requirements. (December 2021) - Khan, Mariam; Al-Absi, Rana S.; Khraisheh, Majeda; Al-Ghouti, Mohammad A.
Abstract: Before investing in any optimizing technology for the recovery and reuse of brine resources, it is of importance to study the full physicochemical characteristics of the brine. In the current study, the physicochemical characteristics of Qatari seawater reverse osmosis (SWRO) brine were fully investigated. The current study intends to lead to a better understanding of the nature of SWRO brine given the economic significance for the country that can be benefited from recycling and reusing various components. The characterization includes physical and chemical composition, as well as mineralogical and morphological investigation. The chemical analysis revealed that the seawater reverse osmosis brine contains various valuable elements and metals such as Ca (77120 mg/L), Na (343500 mg/L), Li (238800 mg/L), Ba (3.3 mg/L), Cs (3.4 mg/L), Fe (30.5 mg/L) and Mg (238800 mg/L). The pH of the brine was 8, while the electrical conductivity and salinity were 90.56 mS/cm and 61.4 ppt, respectively. The scanning electron microscopy-energy-dispersive and energy-dispersive X-ray revealed the placement of various valuable metals on the salt surface. X-ray diffraction showed eight XRD peaks. Interestingly, one peak at 2θ of 31.7° is significantly more intense than the other seven peaks obtained, while all the eight peaks are extremely narrow. The Fourier-transform infrared spectroscopy analysis of the brine sample showed the presence of various functional groups. The narrow and intense peak around 1408 cm −1 confirms the presence of the SO bond in the brine sample, which could correspond to the presence of sulfonyl chlorides or sulfates as indicated by the ICP-OES results. Furthermore, a comparison between the energy requirements for the widely used seawater desalination technologies was presented. Additionally, this study showed the economical and environmental advantages and potential for recovering valuable metals from seawater reverse osmosis brines. Graphical abstract: Image 1